(y-9)-(y+6)=3y

Simplify each term.

Apply the distributive property.

y-9-y-1⋅6=3y

Multiply -1 by 6.

y-9-y-6=3y

y-9-y-6=3y

Simplify by adding terms.

Combine the opposite terms in y-9-y-6.

Subtract y from y.

0-9-6=3y

Subtract 9 from 0.

-9-6=3y

-9-6=3y

Subtract 6 from -9.

-15=3y

-15=3y

-15=3y

Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.

3y=-15

Divide each term in 3y=-15 by 3.

3y3=-153

Cancel the common factor of 3.

Cancel the common factor.

3y3=-153

Divide y by 1.

y=-153

y=-153

Divide -15 by 3.

y=-5

y=-5

Solve for y (y-9)-(y+6)=3y